The Implementation of Pictionary Games to Improve Vocabulary Comprehension - Amelia Yustina Fatmawati; Delsa Miranty; Welliam Hamer (English Department - Universitas Sultan Ageng Tirtayasa, 2022)
Vocabulary is the primary component in learning a language. Vocabulary is essential for getting other skills like speaking, reading, listening, and writing. However, it is not easy to learn vocabulary. Therefore, the teacher should find the teaching technique that makes the student motivated and enthusiastic about learning vocabulary. One technique that can make the students excited and have the motivation to learn a language is by utilizing games. If the teacher uses the game as a technique to teach, the students do not find it easy to get bored. One game that the teacher can use to teach vocabulary is Pictionary games. A Pictionary game is a game that divides the students into groups, one member of the group is assigned to draw a word that the teacher gives, and other members guess the result of the picture. In this conceptual article, the writers aim to help students improve their vocabulary mastery by using Pictionary games.